Deep decarburization recovery method for regenerated electrolyte
By adding decarburized reagents and composite sodium salt to the regenerative electrolyte, combined with low -temperature burning technology, the problem of incomplete carbon remaining in the existing technologies and high energy consumption in the removal of regenerative electrolytes has been solved. , Improved electrolyte performance and production efficiency.
Patent Information
- Application Number
- CN202411529316.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-30
- Publication Date
- 2025-01-28
AI Technical Summary
When removing residual carbon in the regenerated electrolyte after flotation, the prior art has problems such as incomplete removal, high energy consumption, large carbon emissions and possible damage to the electrolyte components, which affects the production efficiency and product quality of the electrolytic aluminum.
By adding decarburized reagents to reduce the carbon content at a lower temperature, the carbon content is mixed with wet method mixing, and the compound sodium salt and electrolyte are fully mixed. Reach the ignition point and contact the air to oxidize, remove the carbon that is difficult to deal with.
Significantly reduce the carbon content in the recycled electrolyte to less than 0.09%, improve the electrolyte performance, reduce energy consumption, avoid secondary pollution, does not change other ingredients in electrolytes, and is suitable for industrial production.
Smart Images

Figure CN119372718A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of methods for treating hazardous waste products from aluminum electrolysis, and in particular relates to a method for deep decarbonization and recovery of regenerated electrolytes. Background Art
[0002] In the production process of electrolytic aluminum industry, anode carbon slag is an inevitable by-product. Its effective treatment and resource utilization are of great significance to improving resource utilization efficiency and reducing environmental pollution. Through flotation technology, regenerated electrolyte rich in electrolyte components can be separated from anode carbon slag. However, although the flotation method has achieved the initial enrichment of regenerated electrolyte to a certain extent, the regenerated electrolyte after flotation still inevitably contains a certain amount of residual carbon (usually about 2%-5%), which has become a key factor restricting its direct reuse in electrolytic aluminum production.
[0003] The presence of residual carbon not only significantly reduces the conductivity of the regenerated electrolyte, resulting in increased energy consumption and decreased current efficiency during the electrolysis process, which in turn affects the production efficiency and product quality of electrolytic aluminum. In addition, the regenerated electrolyte with high carbon content may also damage the cathode and anode materials of the electrolytic cell, shorten the service life of the equipment, and increase maintenance costs.
[0004] In response to the above problems, the industry has tried to use a variety of methods to further treat the regenerated electrolyte after flotation to remove the residual carbon. However, these methods all have limitations to varying degrees: Traditional roasting method: removes carbon through high-temperature oxidation combustion, but the problems of traditional roasting method are incomplete removal, serious stratification, easy hardening of electrolyte, high energy consumption, large carbon emissions, and may destroy the useful components in the regenerated electrolyte, reducing its recycling value. At the same time, the toxic gases and dust generated during the roasting process also cause secondary pollution to the environment.
[0005] Chemical dissolution method: Use acid or alkaline solution to dissolve impurities in the regenerated electrolyte, and then separate them through precipitation, filtration, etc. Although it can effectively remove carbon in theory, the treatment process is complicated and costly, and new impurity elements may be introduced, affecting the quality stability of the regenerated electrolyte.
[0006] Physical separation method (such as grinding, screening, etc.): Although the operation is simple, it is difficult to effectively separate the fine carbon particles in the regenerated electrolyte, and the treatment effect is limited.
[0007] Other new methods: such as ultrasonic-assisted processing and microwave heating, although they have certain research value, have not yet been industrialized, and their technical maturity and economic benefits need to be further verified. Summary of the invention
[0008] The purpose of the present invention is to provide a deep decarbonization and recovery method for regenerated electrolyte, which solves the problem that the existing decarbonization method is prone to secondary pollution and poor effect, greatly reduces the carbon content in the regenerated electrolyte, and improves the electrolyte performance.
[0009] The technical solution adopted by the present invention is: a deep decarbonization and recovery method for regenerated electrolyte, which greatly reduces the carbon content of the regenerated electrolyte at a lower temperature by adding a decarbonization agent, thereby improving the performance of the electrolyte, and fully mixing the composite sodium salt with the electrolyte in a wet mixing manner, calcining, and when the temperature reaches the first interval, loose pores are generated inside and outside the regenerated electrolyte when it agglomerates, separating the regenerated electrolyte from the carbon, releasing the wrapping of the regenerated electrolyte on the carbon, and increasing the contact area between the carbon and the air. When the temperature rises to the second interval temperature, the carbon in the regenerated electrolyte reaches the ignition point and is further oxidized to generate carbon dioxide in contact with the air, thereby removing the difficult-to-handle carbon.
[0010] The first technical solution adopted by the present invention is also characterized in that: Preferably, the regenerated electrolyte deep decarbonization recovery method is implemented in the following steps: Step 1, dissolving a decarbonization reagent in water to obtain a decarbonization solution; Step 2, adding the decarbonization solution to the regenerated electrolyte obtained by flotation, stirring and mixing, to obtain a pre-dried material; Step 3, drying the pre-dried material to obtain a pre-burned material; Step 4, grinding the pre-burned material and calcining it at two temperature intervals, and grinding it after cooling to obtain a low-carbon electrolyte.
[0011] Preferably, the decarbonization reagent is a solid powder combustion aid and a bulking agent, the mass of the decarbonization reagent accounts for 1% to 10% of the mass of the regenerated electrolyte, and the mass of the solvent water is 5 to 8 times that of the decarbonization reagent.
[0012] Preferably, the decarbonation agent is a composite sodium salt, specifically including Na2CO3 and NaHCO3, or Na2CO3 and NaHCO3 plus any one or two of Na2C2O4 or CH3COONa.
[0013] Preferably, the proportion of the composite sodium salt is as follows: Na2CO3 and NaHCO3 account for 90% to 100% of the composite sodium salt, and Na2C2O4 or CH3COONa or the sum of the two account for 0 to 10% of the composite sodium salt.
[0014] Preferably, the decarbonization solution is added to the regenerated electrolyte in a liquid spraying manner, and the liquid mass of the decarbonization solution accounts for 15% to 30% of the mass of the regenerated electrolyte.
[0015] Preferably, step 3 specifically comprises placing the dried material into an alumina sagger, placing it in a forced air drying oven, heating it to 100° C. to 200° C., and dehydrating and drying it.
[0016] Preferably, step 4 is to grind the pre-burned material to 200 mesh, put it into an alumina sagger, place it in a roller kiln, heat it to a first temperature range to make the regenerated electrolyte fluffy, and then heat it to a second temperature range to fully oxidize the carbon into carbon dioxide gas for emission.
[0017] Preferably, in step 4, the temperature in the first interval is 450°C to 550°C, the heating rate is 8-10°C / min, and the insulation time is 30min to 60min; the temperature in the second interval is 600°C to 700°C, the heating rate is 8-10°C / min, and the insulation time is 90min to 150min; the cooling rate during cooling is 10°C / min, the cooling time is 90min, and the furnace temperature is 50°C.
[0018] Preferably, in step 4, composite air is introduced into the kiln, and oxygen in the composite air accounts for 40%-50% of the total gas volume.
[0019] The beneficial effects of the present invention are: The method of the present invention can greatly reduce the carbon content of the regenerated electrolyte at a lower temperature and improve the performance of the electrolyte by adding a decarbonizing agent. The composite sodium salt is fully mixed with the electrolyte in a wet mixing manner, dried and dehydrated, calcined in a roller kiln, and composite air is introduced into the kiln. When the kiln temperature rises to the first interval temperature, the composite sodium salt decomposes to produce gas, so that the regenerated electrolyte produces loose pores inside and outside when agglomerating, separates the regenerated electrolyte from the carbon, releases the regenerated electrolyte from the carbon, increases the contact surface between the carbon and the air, and when the temperature rises to the second interval temperature, the carbon in the regenerated electrolyte reaches the ignition point and contacts the air for further oxidation to generate carbon dioxide, thereby removing the difficult-to-handle carbon. The entire decarbonization process does not use dangerous chemicals such as acids and alkalis, has a low calcination temperature, low energy consumption, simple process, high decarbonization efficiency, no harmful substances are produced during the treatment process, and other components in the regenerated electrolyte are not changed. It can be used or sold directly, and the treated electrolyte carbon content can be reduced to less than 0.09%, which is suitable for industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 It is a schematic flow diagram of the deep decarbonization recovery method of the regenerated electrolyte of the present invention. DETAILED DESCRIPTION
[0021] The technical solution of the present invention will be clearly and completely described below in conjunction with the accompanying drawings.
[0022] The present invention provides a method for recovering regenerative electrolyte by low-temperature decarbonization. The specific process is as follows: Figure 1 As shown, the following steps are included: Step 1: Precisely prepare the decarbonization solution Step 1.1 Accurately weigh a composite sodium salt as a decarbonation reagent in proportion. The composite sodium salt specifically includes Na2CO3 and NaHCO3, or Na2CO3 and NaHCO3 plus any one or two of Na2C2O4 or CH3COONa. The specific proportions are as follows: Na2CO3 and NaHCO3 account for 90% to 100% of the composite sodium salt, and Na2C2O4 or CH3COONa or the sum of the two account for 0 to 10% of the composite sodium salt.
[0023] Step 1.2: According to the specific carbon content of the regenerated electrolyte, the proportion of the decarbonization reagent is adjusted to the optimal range, accounting for 1% to 10% of the mass of the regenerated electrolyte, preferably 1.5% to 10%, so as to minimize the reagent dosage and maximize the decarbonization efficiency.
[0024] Step 1.3 uses deionized water or purified water as a solvent, the mass of which is 5 to 8 times, preferably 6 to 7 times, of the decarbonization reagent to ensure the purity and stability of the decarbonization solution.
[0025] Step 2: Efficient mixing and pre-drying Step 2.1 uses spray drying technology or high-pressure atomization spraying to evenly spray the decarbonization solution on the surface of the regenerated electrolyte to ensure that the decarbonization solution is fully in contact with and penetrates the electrolyte. The liquid mass of the decarbonization solution accounts for 15% to 30% of the mass of the regenerated electrolyte, preferably 20% to 25%.
[0026] Step 2.2: Subsequently, pre-drying is performed in a high-efficiency hot air circulation oven with a set temperature of 100°C to 200°C, preferably 120°C to 180°C. By optimizing the hot air flow rate and circulation mode, the dehydration speed is accelerated and the energy consumption is reduced to obtain a pre-burned material.
[0027] Step 3: Fine grinding and calcination Step 3.1: Use ultrafine grinding equipment to finely grind the pre-burned material, and set the target particle size to above 200 meshes to increase the specific surface area of the material and improve the subsequent calcination efficiency.
[0028] Step 3.2: A multi-temperature zone control system is set in the roller kiln to accurately control the calcination temperature curve. The first temperature zone is set at 450℃~550℃, preferably 480℃~560℃, the heating rate is 8-10℃ / min, and the insulation time is extended to 30min~60min to ensure that the regenerated electrolyte is fully fluffy; the second temperature zone is set at 600℃~700℃, preferably 620℃~780℃, the heating rate is 8-10℃ / min, and the insulation time is adjusted to 90min~150min to completely oxidize carbon impurities and promote the decomposition of other impurities; the third temperature zone is the cooling section, which adopts rapid cooling technology, such as composite air cooling or water quenching cooling, to shorten the cooling time and reduce heat loss.
[0029] Step 4: Optimize gas atmosphere and exhaust gas treatment Step 4.1 During the calcination process, a precisely proportioned composite air is introduced, wherein the oxygen content is set to 45%±5% to balance the oxidation reaction rate and energy consumption.
[0030] Step 4.2 sets up an exhaust gas treatment system to collect and treat carbon dioxide and other harmful gases generated during the calcination process to achieve green production.
[0031] The composition of the present invention is further described below by way of examples and drawings.
[0032] Example 1 Step 1: Accurately weigh the composite sodium salt Na2CO3:NaHCO3:Na2C2O4:CH3COONa = 5:4:0.5:0.5 as a decarbonizing agent. Adjust the decarbonizing agent ratio to 1.5% of the electrolyte mass according to the carbon content of the regenerated electrolyte.
[0033] Step 2: Use deionized water as the solvent, and its mass is 6.5 times that of the decarburizing reagent.
[0034] Step 3: Use spray drying technology to evenly spray the decarbonization solution on the electrolyte, and the mass of the solution is 22% of the mass of the electrolyte.
[0035] Step 4: Pre-dry in a hot air circulation oven at 150°C, optimizing the hot air flow to ensure rapid dehydration.
[0036] Step 5: Finely grind the pre-sintered material to 200 mesh.
[0037] Step 6: The first temperature zone of the roller kiln is set to 500°C, the heating rate is 8°C / min, and the temperature is kept for 45 minutes; the second temperature zone is set to 650°C and the temperature is kept for 120 minutes; the cooling section uses composite air with an oxygen content of 45% for rapid cooling to obtain the final product.
[0038] Example 2 Step 1: Accurately weigh the composite sodium salt Na2CO3:NaHCO3 = 1:1 as a decarbonizing agent. According to the carbon content of the regenerated electrolyte, the proportion of the decarbonizing agent is adjusted to 5% of the electrolyte mass.
[0039] Steps 2 to 6: remain the same as Example 1.
[0040] Example 3 Step 1: Accurately weigh the composite sodium salt Na2CO3:NaHCO3:Na2C2O4:CH3COONa = 8:6:0.5:0.5 as a decarbonizing agent. Adjust the decarbonizing agent ratio to 5% of the electrolyte mass according to the carbon content of the regenerated electrolyte.
[0041] Steps 2 to 6: remain the same as Example 1.
[0042] Example 4 Step 1: Accurately weigh the composite sodium salt Na2CO3:NaHCO3:Na2C2O4:CH3COONa = 5:5:0.5:0.5 as a decarbonizing agent. Adjust the decarbonizing agent ratio to 10% of the electrolyte mass according to the carbon content of the regenerated electrolyte.
[0043] Steps 2 to 6: remain the same as Example 1.
[0044] Example 5 Steps 1 to 5: remain the same as Example 1.
[0045] Step 6: The first temperature zone of the roller kiln is set to 450°C, the heating rate is 8°C / min, and the temperature is kept for 45 minutes; the second temperature zone is set to 650°C, the heating rate is 8°C / min, and the temperature is kept for 120 minutes; the cooling section uses composite air with an oxygen content of 45% for rapid cooling to obtain the final product.
[0046] Example 6 Steps 1 to 5: remain the same as Example 1.
[0047] Step 6: The first temperature zone of the roller kiln is set to 550°C, the heating rate is 8°C / min, and the temperature is kept for 45 minutes; the second temperature zone is set to 650°C and the temperature is kept for 120 minutes; the cooling section uses composite air with an oxygen content of 45% for rapid cooling to obtain the final product.
[0048] Example 7 Step 1: Keep the same as Example 1.
[0049] Step 2: Use deionized water as solvent, the mass of which is 5 times that of the decarburizing reagent.
[0050] Step 3: Use spray drying technology to evenly spray the decarbonization solution on the electrolyte, and the mass of the solution is 15% of the mass of the electrolyte.
[0051] Step 4: Pre-dry in a hot air circulation oven at 100°C, optimizing the hot air flow to ensure rapid dehydration.
[0052] Step 5: Keep the same as Example 1.
[0053] Step 6: The first temperature zone of the roller kiln is set to 500°C, the heating rate is 9°C / min, and the temperature is kept for 30 minutes; the second temperature zone is set to 600°C, the heating rate is 9°C / min, and the temperature is kept for 90 minutes; the cooling section uses composite air with an oxygen content of 40% for rapid cooling to obtain the final product.
[0054] Example 8 Step 1: Keep the same as Example 1.
[0055] Step 2: Use deionized water as solvent, the mass of which is 8 times that of the decarburizing reagent.
[0056] Step 3: Use spray drying technology to evenly spray the decarbonization solution on the electrolyte, and the mass of the solution is 30% of the mass of the electrolyte.
[0057] Step 4: Pre-dry in a hot air circulation oven at 200°C, optimizing the hot air flow to ensure rapid dehydration.
[0058] Step 5: Keep the same as Example 1.
[0059] Step 6: The first temperature zone of the roller kiln is set to 500°C, the heating rate is 10°C / min, and the temperature is kept for 60 minutes; the second temperature zone is set to 700°C, the heating rate is 10°C / min, and the temperature is kept for 150 minutes; the cooling section uses composite air with an oxygen content of 50% for rapid cooling to obtain the final product.
[0060] Comparative Example 1 Step 1: Finely grind the pre-sintered material to 200 mesh.
[0061] Step 2: The roller kiln temperature is set to 860°C, the heating rate is 8°C / min, and the temperature is kept for 150 minutes; the cooling section uses air for rapid cooling to obtain the final product.
[0062] Table 1
[0063] As can be seen from Table 1 above, by using composite sodium salts (Na2CO3, NaHCO3, Na2C2O4, CH3COONa) as decarbonization agents and combining them with a low-temperature calcination process, the carbon content can be greatly reduced to below 0.09% without changing other components in the regenerated electrolyte. This effect is significantly better than traditional methods and effectively improves the performance of the electrolyte. At the same time, the entire decarbonization process is completed at a relatively low temperature (up to 700°C), which significantly reduces energy consumption compared to high-temperature calcination. In addition, the efficiency and thoroughness of the decarbonization process are ensured by heating up in stages (including the fluffy stage and the fully oxidized stage).
Claims
1. A method for deep decarbonization and recovery of regenerated electrolyte, characterized in that: By adding a decarbonizing agent, the carbon content of the regenerated electrolyte can be greatly reduced at a lower temperature, thereby improving the performance of the electrolyte. The composite sodium salt is fully mixed with the electrolyte by a wet mixing method and calcined to a temperature in the first interval, so that loose pores are generated inside and outside the regenerated electrolyte when it agglomerates, separating the regenerated electrolyte from the carbon, releasing the regenerated electrolyte from the carbon, and increasing the contact area between the carbon and the air. When the temperature rises to a temperature in the second interval, the carbon in the regenerated electrolyte reaches the ignition point and is further oxidized to generate carbon dioxide in contact with the air, thereby removing the difficult-to-handle carbon.
2. The deep decarbonization recovery method of regenerated electrolyte according to claim 1, characterized in that: Please follow the steps below to implement: Step 1, dissolving a decarbonization reagent in water to obtain a decarbonization solution; Step 2, adding the decarbonization solution to the regenerated electrolyte obtained by flotation, stirring and mixing, to obtain a pre-dried material; Step 3, drying the pre-dried material to obtain a pre-burned material; Step 4, grinding the pre-burned material and calcining it at two temperature intervals, and grinding it after cooling to obtain a low-carbon electrolyte.
3. The deep decarbonization recovery method of regenerated electrolyte according to claim 2, characterized in that: In the step 1, the decarbonization reagent is a solid powder combustion aid and a bulking agent, the mass of the decarbonization reagent accounts for 1% to 10% of the mass of the regenerated electrolyte, and the mass of the solvent water is 5 to 8 times that of the decarbonization reagent.
4. The deep decarbonization recovery method of regenerated electrolyte according to claim 3, characterized in that: In step 1, the decarbonization reagent is a composite sodium salt, specifically including Na2CO3 and NaHCO3, or Na2CO3 and NaHCO3 plus any one or two of Na2C2O4 or CH3COONa.
5. The deep decarbonization recovery method of regenerated electrolyte according to claim 4, characterized in that: The proportions of the composite sodium salt are as follows: Na2CO3 and NaHCO3 account for 90% to 100% of the composite sodium salt, and Na2C2O4 or CH3COONa or the sum of the two account for 0 to 10% of the composite sodium salt.
6. The deep decarbonization recovery method of regenerated electrolyte according to claim 2, characterized in that: In the step 2, the decarbonization solution is added to the regenerated electrolyte in a liquid spraying manner, and the liquid mass of the decarbonization solution accounts for 15% to 30% of the mass of the regenerated electrolyte.
7. The deep decarbonization and recovery method of regenerative electrolyte according to claim 2, characterized in that: The step 3 specifically includes placing the dried material into an alumina sagger, placing it in a blast drying oven, heating it to 100° C. to 200° C., and dehydrating and drying it.
8. The deep decarbonization and recovery method of regenerative electrolyte according to claim 2, characterized in that: The step 4 is specifically to grind the pre-burned material to 200 mesh, put it into an alumina sagger, place it in a roller kiln, heat it to a first interval temperature to make the regenerated electrolyte fluffy, and then heat it to a second interval temperature to fully oxidize the carbon into carbon dioxide gas for emission.
9. The deep decarbonization and recovery method of regenerated electrolyte according to claim 8, characterized in that: In step 4, the temperature in the first interval is 450°C to 550°C, the heating rate is 8-10°C / min, and the insulation time is 30min to 60min; the temperature in the second interval is 600°C to 700°C, the heating rate is 8-10°C / min, and the insulation time is 90min to 150min; the cooling rate during cooling is 10°C / min, the cooling time is 90min, and the furnace temperature is 50°C.
10. The deep decarbonization and recovery method of regenerated electrolyte according to claim 9, characterized in that: In step 4, composite air is introduced into the kiln, and oxygen in the composite air accounts for 40%-50% of the total gas volume.